Vývoj, optimalizace a validace analytické metody na stanovení kyseliny chikorové a dalších derivátů kyseliny kávové pomocí LC/MS - Pazderková, Nela (Jihočeská univerzita, 2021)
This thesis deals with the development, optimization, and validation of an analytical method for the determination of chicoric acid and other caffeic acid derivates using LC/MS. First, the development and optimization of the analytical method was conducted. The following parameters were selected for the optimization: mobile phase composition and flow rate injection volume capillary temperature, voltage S-lens and F-lens voltage, ion injection time, product ion selection, and collision energy. Then, the analytical method was successfully validated and tested for quantitative analysis in a range of Echinacea food matrixes - tea, tablet, and tincture.
Development, optimization and validation of an analytical method for determination of chicoric acid and other caffeic acid derivatives using LC/MS
Keywords: Kyselina chikorová; kyselina kávová; kyselina kaftarová; kyselina chlorogenová; cynarin; echinakosid; antioxidanty; hmotnostní spektrometrie; kapalinová chromatografie; optimalizace; validace.; Chicoric acid; caffeic acid; caftaric acid; chlorogenic acid; cynarin; echinacosid; antioxidants; mass spectrometry; liquid chromatography; optimization; validation.